Role and Application of Diffusion-weighted Imaging in Evaluation of Prostate Cancer - Lahoti, Amol Madanlal; Lakhotiya, Ankita Ramprasad; Ingole, Sarang Manohar; Dhok, Avinash Parshuram; Mudaliar, Prashant N (Indian Journal of Medical and Paediatric Oncology, 2018)
Introduction: Diffusion-weighted imaging (DWI) is an important part of magnetic resonance imaging (MRI) in the evaluation of specific organs, including the breast, kidney, liver, and prostate. Prostate cancer lesions are composed of tightly packed cells with reduced extracellular space, which can be visualized on DWIs as areas of restricted diffusion (i.e., high-signal intensity), with corresponding low-signal intensity on apparent diffusion coefficient (ADC) maps and low mean ADC value. Objective: The objective of this study is to identify the appropriate cutoff and mean ADC value to diagnose neoplastic prostatic lesions in central India. Materials and Methods: Sixty-six patients with suspected prostatic pathology were included in this study. All patients underwent MRI on a 1.5-T scanner with a phased-array body coil. MRIs were evaluated compared with the histopathological staging. Results:: The diagnostic accuracy of DWI in predicting malignancy was 39/41, i.e., 95.12%, which is the positive predicted value. The mean ADC for benign category was 1.14 with standard deviation (SD) of 0.14 while mean for prostatitis was 0.91 with SD of 0.26 and for carcinoma was 0.75 with SD of 0.19. The difference in the means was statistically highly significant. Conclusion: DWI demonstrates the restriction of diffusion and the reduction of ADC values in neoplastic tissue and improves the diagnostic accuracy in lesion characterization. This technique allows short acquisition time and provides high-contrast resolution between neoplastic and normal tissue. This technique can be a useful adjunct to the established dynamic contrast-enhanced-MRI.
Keywords: Apparent diffusion coefficient; diffusion-weighted imaging; prostate cancer; prostate pathologies